Reviewing the link between language abilities and peer relations in children with developmental language disorder: The importance of children's own perspectives. (June 2021) - Janik Blaskova, Lenka; Gibson, Jenny L
Background and aims: Children with developmental language disorder (DLD) are at risk of difficulties in their friendships and peer relations. The present review explores how research directly involving children with DLD can inform our understanding of peer relations in this group, and how research insights may change according to the nature of their involvement in the studies. We further examine how these findings might shape current theoretical understandings of the links between language impairment and peer relations. Methods: An integrative review methodology was used in order to identify relevant studies and synthesise the findings. A structured database search was carried out using the qualitative PICo framework; Population = 4–12-year-old children with DLD, phenomenon of Interest = peer relations, Context = research studies directly including children. After screening, 52 studies were included in a narrative research synthesis. Main contribution: We identified six main types of study that directly included children with DLD; interview, sociometric, self-report, task-based, naturalistic observation and staged observation. Interview-based studies were the most likely to use a meaningful participatory approach. Indications of good practices for participation included reporting on involvement practices, seeking child assent, adapting materials and language used, using visual supports, using child-preferred communication methods and using art-based approaches. Findings from the narrative synthesis of studies highlight the importance of friendships to quality of life, and the role of pragmatic language skills and self-perceptions in building friendships. Conclusions: Research on the peer relations of children with DLD is in the early stages when it comes to taking a participatory approach, however there are some examples of inclusive practice from which the whole field can learn. The findings show that research that directly includes children with language disorders and takes account of their communication challenges can help build a more comprehensive knowledge of their world and leads to interesting avenues for interventions targeting social adjustment. Implications: Clinical implications are discussed with reference to the highlighted pragmatic language and social needs of children with DLD, which are typically not addressed unless disproportionately affected in comparison to structural language impairments.